2017
DOI: 10.1002/ijgo.12397
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective multicenter study of leaving the placenta in situ for patients with placenta previa on a cesarean scar

Abstract: Leaving the placenta in situ, with close postpartum follow-up for at least several months, could be a uterus-preserving option for patient with PAS disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…However, an experienced acoucher should be able to diagnose the vast majority of AIP cases clinically at laparotomy (See point 14) and subsequent histopathological findings from cases of 'failed' expectant management suggest that the risk of misdiagnosis is very low. For this case series, 37 Another smaller study of 36 women managed conservatively reported a success rate of 69% 38 (level 2b evidence). Three reviews of published case series report success rates of 85% 39 , 58% 40 and 60% 41 .…”
Section: Accepted Manuscriptmentioning
confidence: 81%
“…However, an experienced acoucher should be able to diagnose the vast majority of AIP cases clinically at laparotomy (See point 14) and subsequent histopathological findings from cases of 'failed' expectant management suggest that the risk of misdiagnosis is very low. For this case series, 37 Another smaller study of 36 women managed conservatively reported a success rate of 69% 38 (level 2b evidence). Three reviews of published case series report success rates of 85% 39 , 58% 40 and 60% 41 .…”
Section: Accepted Manuscriptmentioning
confidence: 81%
“…Another smaller study of 36 women managed conservatively reported a success rate of 69% 38 (level 2b evidence). Three reviews of published case series report success rates of 85% 39 , 58% 40 and 60% 41 .…”
Section: Is Expectant Management Of Clinically Confirmed Aip Effective and Does It Reduce Maternal Morbidity When Compared To Surgical Trmentioning
confidence: 99%
“…Numerous studies [11,12] showed that conservative approach (with or without partial resection of placenta) was a uterus-preserving option for patient with PAS disorders. Nevertheless PAS disorders managed with the placenta left in situ require close follow-up monitor and it takes at least several months after delivery before placental resorption was achieved [13]. Moreover maternal morbidity and mortality is not rare in the placenta left in situ approach [14].…”
Section: Discussionmentioning
confidence: 99%